Treatment Outcomes in Multidrug-Resistant Tuberculosis - Günther, Gunar; Lange, Christoph; Alexandru, Sofia; Altet, Neus; Avsar, Korkut; Bang, Didi; Barbuta, Raisa; Bothamley, Graham; Ciobanu, Ana; Crudu, Valeriu; Danilovits, Manfred; Dedicoat, Martin; et al. (The New England journal of medicine, 2016)
Multidrug-resistant tuberculosis is a major global challenge. This report examines the definition of treatment success and its effect on determining cure. To the Editor: Despite lengthy treatment with costly second-line drug regimens, curing multidrug-resistant (MDR) tuberculosis (bacillary resistance to at least isoniazid and rifampin) remains a challenge. 1 The World Health Organization (WHO) defines “cure” as “treatment completion” with at least three negative cultures after the intensive phase of therapy in the absence of “treatment failure.” The definition of “treatment failure” requires early termination of treatment or the need for permanent regimen change of at least two antituberculosis drugs. “Treatment success” is defined as the sum of cure and treatment completion. 2 We evaluated treatment outcomes according to WHO definitions in the TBNET . . .